Work in deregulated labour markets: A research agenda for precariousness - Valeria Pulignano (European Trade Union Institute (ETUI), 2019)
The traditional dichotomy of paid versus unpaid work has a tendency to marginalise unpaid work when we attempt to conceptualise precariousness, leading to our perception that it involves exposure to the unpredictability of an individual's future. A new theoretical and empirical perspective is thus required - one that breaks with the distinction between paid and unpaid work and rethinks precariousness in terms of the paid-unpaid continuum of work by identifying the unpaid activities that increasingly underlie paid employment as a source of 'value' creation in a deregulated labour market. This paper proposesan original heuristic analytical framework for the study of precariousness within the continuum of paid and unpaid work, while presenting its features, explaining the various underlying motives and shedding light on its scientific and policyrelated dimensions.
Keywords: 330; atypical employment; Deregulation; labor market flexibility; Operational value creation; Atypische Beschäftigung; Deregulierung; Arbeitsmarktflexibilität; Betriebliche Wertschöpfung